Gene therapy in patients with transfusion-dependent β-thalassemia - Thompson, Alexis A.; Kalle, Christof von (The New England journal of medicine, 2018)
BACKGROUND Donor availability and transplantation-related risks limit the broad use of allogeneic hematopoietic-cell transplantation in patients with transfusion-dependent β-thalassemia. After previously establishing that lentiviral transfer of a marked β-globin (βA-T87Q) gene could substitute for long-term red-cell transfusions in a patient with β-thalassemia, we wanted to evaluate the safety and efficacy of such gene therapy in patients with transfusiondependent β-thalassemia. - METHODS In two phase 1-2 studies, we obtained mobilized autologous CD34+ cells from 22 patients (12 to 35 years of age) with transfusion-dependent β-thalassemia and transduced the cells ex vivo with LentiGlobin BB305 vector, which encodes adult hemoglobin (HbA) with a T87Q amino acid substitution (HbAT87Q). The cells were then reinfused after the patients had undergone myeloablative busulfan conditioning. We subsequently monitored adverse events, vector integration, and levels of replication-competent lentivirus. Efficacy assessments included levels of total hemoglobin and HbAT87Q, transfusion requirements, and average vector copy number. - RESULTS At a median of 26 months (range, 15 to 42) after infusion of the gene-modified cells, all but 1 of the 13 patients who had a non-β0/β0 genotype had stopped receiving red-cell transfusions; the levels of HbAT87Q ranged from 3.4 to 10.0 g per deciliter, and the levels of total hemoglobin ranged from 8.2 to 13.7 g per deciliter. Correction of biologic markers of dyserythropoiesis was achieved in evaluated patients with hemoglobin levels near normal ranges. In 9 patients with a β0/β0 genotype or two copies of the IVS1-110 mutation, the median annualized transfusion volume was decreased by 73%, and red-cell transfusions were discontinued in 3 patients. Treatment-related adverse events were typical of those associated with autologous stem-cell transplantation. No clonal dominance related to vector integration was observed. The authors’ full names, academic degrees, and affiliations are listed in the Appendix. Address reprint requests to Dr. Thompson at the Ann and Robert H. Lurie Children’s Hospital of Chicago, Hematology-Oncology, 225 E. Chicago Ave., Box 30, Chicago, IL 60611, or at a-thompson northwestern.edu; to Dr. Walters at mwalters@mail.cho.org; to Dr. Leboulch at pleboulch@rics.bwh.harvard.edu; or to Dr. Cavazzana at m.cavazzana@aphp.fr. Drs. Thompson, Walters, Leboulch, and Cavazzana and Drs. Kwiatkowski, Rasko, and Ribeil contributed equally to this article. N Engl J Med 2018;378:1479-93. DOI: 10.1056/NEJMoa1705342 Copyright © 2018 Massachusetts Medical Society. - CONCLUSIONS Gene therapy with autologous CD34+ cells transduced with the BB305 vector reduced or eliminated the need for long-term red-cell transfusions in 22 patients with severe β-thalassemia without serious adverse events related to the drug product. (Funded by Bluebird Bio and others; HGB-204 and HGB-205 ClinicalTrials.gov numbers, NCT01745120 and NCT02151526.)